Changes in ventricular–arterial coupling during decongestive therapy in acute heart failure. (October 2014) - Berthelot, Emmanuelle; Bihry, Nicolas; Brault‐Melin, Ophelie; Assayag, Patrick; Cohen‐Solal, Alain; Chemla, Denis; Logeart, Damien
Abstract Aims Coupled arterial and left ventricular properties are poorly documented in acute heart failure. The aim of this prospective noninvasive study was to document early changes in ventricular–arterial coupling in patients with acutely decompensated HF (ADHF). Methods and Results We studied 19 patients hospitalized for ADHF (age 62 ± 15 years, NYHA class 3 or 4). Patients with shock and sustained arrhythmias were excluded. All the patients received intravenous loop diuretics, and none received intravenous vasodilators or inotropes. Ongoing chronic treatments were maintained. Echocardiography and radial artery tonometry were performed simultaneously on admission and after clinical improvement (day 4 ± 1 after admission). Classical echocardiographic parameters were measured, including stroke volume (SV). End‐systolic pressure (Pes) was derived from reconstructed central aortic pressure, and arterial elastance (Ea) was calculated as Ea = Pes/SV. End‐systolic LV elastance (Ees) was calculated with the single‐beat method. Ventricular–arterial coupling was quantified as the Ea/Ees ratio. Following IV diuretic therapy, mean weight loss was 5 ± 2 kg (P < 0·01) and BNP fell from 1813 (median) (IQR = 1284–2342) to 694 (334–1053) pg/mL (P < 0·01). Ea fell by 29%, from 2·46 (2·05–2·86) to 1·78 (1·55–2·00) mmHg/mL (P < 0·01), while Ees remained unchanged (1·28 (1·05–1·52) to 1·13 (0·92–1·34) mmHg/mL). The Ea/Ees ratio therefore fell, from 2·13 (1·70–2·56) to 1·81 (1·56–2·08) (P < 0·02). Conclusion An early improvement in ventricular–arterial coupling was observed after diuretic‐related decongestive therapy in ADHF patients and was related to a decrease in effective arterial elastance rather than to change in LV contractility.